REFLECTIONS OF SOCIAL WORKERS ON THE EXPERIENCES OF PREGNANT TEENAGERS DURING GROUP WORK SESSIONS - Skobi, Freddy; Makofane, Mankwane (Social Work/Maatskaplike Werk, 2017)
This paper focuses on the reflections of 12 social workers, based on group sessions held with pregnant teenagers in the Capricorn district, Limpopo Province. The burden of caring for pregnant teenagers and their children falls on their families and the state, while men, young and old, are not held responsible. Although some of the literature pertaining to the health sector does not recognise or acknowledge social work, the multifaceted challenges facing teenagers, including the prevention of repeat pregnancies during adolescence call for a multidisciplinary and inter-sectoral approach to support these young women. Future research should focus on, among other things, developing resilience among teenagers.